Memperkuat Tata Kelola Pemerintahan Daerah Untuk Penanggulangan Kemiskinan Berkelanjutan: Studi Kasus di Kabupaten Jeneponto - Mubaraq, Ahmad Zihar; Thaha, Rasyid; Saputra, Irwan Ade (Development Policy and Management Review (DPMR), 2025)
Abstract Poverty remains one of the fundamental challenges faced by local governments, including Jeneponto Regency, which continues to record a relatively high poverty rate compared to other regions in South Sulawesi Province. This study aims to analyze the role of the Jeneponto Regency Government in poverty reduction efforts and to identify factors influencing the effectiveness of its programs. Employing a qualitative approach, data were collected through in-depth interviews, observation, and documentation involving key informants from local government officials and program beneficiaries. The findings reveal that the local government has undertaken significant initiatives through the implementation of social assistance programs, community economic development, and the enhancement of infrastructure and basic services. However, several challenges hinder program success, including budget constraints, weak inter-agency coordination, and limited community participation. The study recommends strengthening institutional synergy, improving bureaucratic capacity, and encouraging active community engagement in all stages of program implementation to achieve more effective and sustainable poverty alleviation.   Abstrak Kemiskinan merupakan salah satu permasalahan mendasar yang dihadapi oleh daerah, termasuk Kabupaten Jeneponto, yang dikenal memiliki tingkat kemiskinan relatif tinggi dibanding kabupaten lain di Provinsi Sulawesi Selatan. Penelitian ini bertujuan untuk menganalisis peran Pemerintah Daerah Kabupaten Jeneponto dalam upaya penanggulangan kemiskinan, serta mengidentifikasi faktor-faktor yang memengaruhi efektivitas program-program tersebut. Penelitian ini menggunakan pendekatan kualitatif dengan teknik pengumpulan data melalui wawancara mendalam, observasi, dan dokumentasi, serta melibatkan berbagai informan dari unsur pemerintah daerah dan masyarakat penerima program. Hasil penelitian menunjukkan bahwa Pemerintah Daerah Jeneponto telah menjalankan peran penting melalui pelaksanaan program bantuan sosial, pengembangan ekonomi masyarakat, serta peningkatan kualitas infrastruktur dan layanan dasar. Namun, masih terdapat berbagai kendala yang memengaruhi keberhasilan program, seperti keterbatasan anggaran, kurangnya koordinasi antar instansi, serta lemahnya partisipasi masyarakat. Penelitian ini menyarankan perlunya penguatan sinergi kelembagaan, peningkatan kapasitas aparatur, serta pelibatan aktif masyarakat dalam setiap tahapan program sebagai strategi penanggulangan kemiskinan yang lebih efektif dan berkelanjutan.